Desain dan Analisa Press Tool Front Plate 3TP038 menggunakan Software CAD/CAE pada Perusahaan Manufaktur Loudspeaker - Dinda Aksari; Pranowo Sidi; Bayu Wiro Karuniawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Loudspeaker Manufacturing Company is one of the companies engaged in the manufacture of loudspeakers that make components and assemblies for loudspeakers. One part of the loudspeaker is the front plate with tool number 03TP038 which is produced with a press system through two separate procedures and is carried out with two separate tools and work stations. This causes the production process to be less efficient. Press tool design and analysis using CAD / CAE software is an effort made to optimize the production process by designing the press tool into a progressive tool. As well as the strength analysis in the design is used as a determination of feasibility, as well as improvements to the press tool. The results of the study that the Front Plate 3TP038 Press Tool design can be made into a progressive tool by performing the required calculations. The simulation results obtained the maximum value of von Mises stress on the piercing punch Ø14.18 mm is 244.1 Mpa deflection 0.0187 mm, piercing punch Ø2.08 mm is 539.9 Mpa deflection 0.05034, punch fillet R0.3 mm is 72.29 MPa deflection 0.004137, punch fillet R0.3 mm bottom is 406.9 Mpa deflection 8.196e-004 mm, Blanking Punch Ø40.67 mm is 194.3 Mpa deflection 0.007589, dies at 283.5 Mpa deflection is 0.003973 where the value does not exceed the yield strength value of D2 Steel material which is 2150 Mpa